Comprehensive and Innovative Language Learning Model with an Intercultural Communication Approach: A Systematic Review of Anecdotal Text Writing Lessons in Secondary Schools - Rajaguk-guk, Sastri Br; Iskandar, Ifan; Hakim, Muhammad Kamal bin Abdul (CV. Publikasi Indonesia, 2025)
This research investigates the effectiveness of various language learning models in improving students' skills in writing anecdotal texts at the secondary school level. The primary research problem addresses the gap in the existing teaching methods for anecdotal text writing and the need for innovative, intercultural, and project-based learning models. The objective of the research is to evaluate the impact of project-based learning, technology, and intercultural communication strategies on students' writing and critical thinking abilities. The research method used is a Systematic Literature Review (SLR), analyzing 50 relevant articles published in the last five years. Results show that project-based learning models and technology such as Grammarly and other digital media can improve students' writing and critical thinking skills. The intercultural approach also plays an important role in building cross-ethnic cultural understanding between teachers and students. However, there are limitations on the implementation of technology and generalization of research results, so further research is needed for the development of a more inclusive model.